Genomic mutations in oral poliovirus vaccine strains : implications for the eradication of poliovirus - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2013)
Thesis (PhD (Medical Virology))--University of Pretoria, 2004.